A Review of Fresh Market Sweet Corn Production and Price Trends from 2010 to 2022: FE1149, 9/2024 - Amon, Kelvin; Wade, Tara; Mészáros, Anna; Rumenik, Tori (EDIS, 2024)
This publication provides information on conventional fresh market sweet corn acreage, volume, and pricing for the top four producing states: California, Florida, Georgia, and New York. (Other states produce a substantial amount of processed market sweet corn but are not the focus here.) This is one in a series of Ask IFAS publications focused on trends in Florida’s five most economically important specialty crops (excluding citrus): fresh market sweet corn, bell peppers, tomatoes, watermelons, and strawberries. This information will be useful to producers, Extension agents, and others interested in trends concerning specialty crop commodities. This publication serves as a unique source summarizing important information about the specialty crop market and production trends.